ANTENATAL INVESTIGATION OF DUCTUS VENOSUS VELOCITY AS A METHOD OF DETECTING THE FETAL HEART FAILURE, CAUSED BY PARVOVIRUS B19 INFECTION - Bondarenko, N. P.; Aksonova, A. V. (International Journal of Medicine and Medical Research, 2017)
Background. The article describes the methods and results of investigation of blood flow velocity waveforms in fetal ductus venosus (DV). These studies are used to visualize the degree of fetal heart failure and determine its further clinical course. Objective. The study was aimed to predict the development of heart failure in the fetuses that were infected with parvovirus B19 infection during 11-14 gestation weeks by measuring the Doppler parameters of blood flow velocity in the DV. Methods. Our investigation involved 20 pregnant women aged from 18 to 30 years old who were infected with parvovirus B19 infection during the period from 11 to 14 weeks of gestation. The DV was determined by means of color Doppler. Fetal echocardiography (EchoCG) was performed by means of the ultrasound scanner Philips HD IIXE device (USA) using a transabdominal convex probe with the frequency of 3.5 MHz, operating in a CDC mode and the frequency filter at 100 Hz. The A-wave directivity evaluation in the DV was investigated according to the Guideline Principles of the Fetal Medicine Foundation (www.fetalmedicine.com). Statistical processing of data was carried out using the package of applied programs Microsoft Office Excel 2016 and Statistica 6, Stata 12. Results. In 16 of 20 (80%) fetuses we did not observe any absent or reversed A-wave flow in the DV during atrial contraction as well as any fetal echocardiographic pathological signs. In 2 (10%) cases a reversed A-wave flow in the DV in a combination with EchoCG-signs of overload of left side of heart, resulting in enlargement (dilatation) of left atrium and left ventricle were detected. In 2 (10%) cases the presence of a reversed A-wave flow in the DV and EchoCG-signs of fetal heart failure (reduction of cardiac output, significant dilatation of left ventricle) were evidenced. The results of the study confirm that with the expansion of fetal nuchal translucency thickness, the systolic blood flow velocity in the DV increases with the correlation coefficient r=0.594, which proves a linear dependence between these two ultrasonography parameters. Conclusions. The linear correlation between the presence of a reversed A-wave blood flow velocity in the DV and the overload of left side of fetal heart, development of heart failure (20% of the total number of examined women) were proved.